Negara Ideal : Menurut Pemikiran Muhammad Natsir dan Soekarno - Utin Dila Mantajai; Selvani Selvani; Umu Habibah; Surya Sukti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the concept of an ideal state according to the thoughts of Muhammad Natsir and Soekarno, who have fundamental differences in their views on the relationship between religion and the state. The research problem focuses on how these two figures formulate the concept of an ideal state and what the similarities and differences are. This study uses a qualitative method with a literature review approach, analyzing various sources such as books and academic journals. The results show that Muhammad Natsir views the state as an instrument to implement Islamic values in governance, making religion and state inseparable. In contrast, Soekarno emphasizes the importance of separating religion and state to maintain unity in a diverse society and avoid the politicization of religion. Despite these differences, both thinkers share the same goal: to establish a just, prosperous, and welfareoriented state. Therefore, the ideas of these two figures provide significant insights into understanding the concept of an ideal state in the Indonesian context.